Fluorescent / colorimetric dual-mode sensor for hydrogen sulfide detection and preparation method of fluorescent / colorimetric dual-mode sensor

By combining gold nanoclusters with lead-based metal-organic frame materials and making fluorescent/colorimetric dual-mode sensors, the stability and sensitivity problems of fluorescent sensors in the current technology in hydrogen sulfide detection are solved, and efficient and real-time hydrogen sulfide detection is achieved.

CN119757293AActive Publication Date: 2025-04-04ZHEJIANG UNIV

Patent Information

Application Number
CN202411890748.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-04
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

In the detection of hydrogen sulfide, existing fluorescence sensors have problems such as complex synthesis, poor optical stability, weak single-channel signal interference and susceptible to external light sources, and the luminous efficiency of gold nanoclusters is low.

Method used

By in situ composite of gold nanoclusters with lead-based metal-organic frame material, the gold nanocluster/metal-organic frame composite material is constructed and mixed with sodium alginate to make a cast film liquid. A fluorescent/colorimetric dual-mode sensor is obtained by scraping and molding.

Benefits of technology

It significantly improves the luminescence efficiency of gold nanoclusters, realizes high sensitivity and high selectivity detection of hydrogen sulfide, has anti-interference ability and fast response characteristics, and can be detected under real-time portable conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119757293A_ABST
    Figure CN119757293A_ABST
Patent Text Reader

Abstract

The invention discloses a fluorescent / colorimetric dual-mode sensor for hydrogen sulfide detection and a preparation method of the fluorescent / colorimetric dual-mode sensor. The method comprises the following steps: performing in-situ synthesis on gold nanoclusters and a metal-organic framework material to obtain a gold nanocluster / metal-organic framework composite material, uniformly mixing the composite material with sodium alginate to obtain a membrane casting solution, dripping the membrane casting solution on a substrate, and performing blade coating, forming and cleaning to obtain the gold nanocluster / metal-organic framework composite membrane. The gold nanocluster / metal-organic framework hydrogel film sensor is obtained. The fluorescence property of the sensor is remarkably improved, the sensor can quickly respond to hydrogen sulfide on fluorescence and colorimetric channels, and the sensor has the advantages of high sensitivity, high selectivity and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fluorescence sensing and relates to a fluorescence / colorimetric dual-mode sensor for hydrogen sulfide detection and a preparation method thereof. Background Art

[0002] Hydrogen sulfide (H2S) is a colorless, toxic, flammable gas that smells like rotten eggs at low concentrations. It is mainly produced in industries such as mining, pigment processing, and oil refining, posing a serious threat to human health and the environment. Even exposure to low concentrations of hydrogen sulfide can have adverse effects on the eyes and respiratory system, while high concentrations can cause asthma, coma, suffocation, and even death. Therefore, the U.S. Occupational Safety and Health Act (OSHA) stipulates that the permissible occupational exposure limit for hydrogen sulfide is 10 ppm for 8 hours. At the same time, hydrogen sulfide is also an endogenous gaseous transmitter present in mammalian tissues, playing a vital role in various physiological and pathological processes. Abnormal hydrogen sulfide levels are associated with a variety of diseases such as Alzheimer's disease, asthma, cirrhosis, and diabetes. Considering the environmental and physiological importance of hydrogen sulfide, it is of great significance to develop simple, efficient, and real-time hydrogen sulfide monitoring technology.

[0003] Compared with traditional hydrogen sulfide detection techniques such as chromatography and electrochemistry, these techniques are often limited by complex operations, high costs, bulky equipment, and low sensitivity. Fluorescence probe-based analysis has become a more suitable method for on-site detection due to its rapid response, easy operation, and visualization. However, these fluorescent sensors still face challenges such as complex synthesis, poor optical stability, and weak single-channel signal interference in practical applications. In addition, fluorescence detection is easily interfered by external light sources and needs to be operated in a dark environment. Taking gold nanoclusters (AuNCs) as an example, they have received widespread attention in H2S detection due to their low toxicity, large Stokes shift, excellent photostability, and good biocompatibility. However, the luminescence efficiency of AuNCs is still relatively low due to the excessive energy loss of ligand motion.

[0004] Based on this, the present invention uses porous materials to fix AuNCs, and embeds AuNCs into porous materials to improve their luminescence efficiency by utilizing the spatial confinement effect. Porous MOFs are assembled from metal ions and organic ligands, and have the advantages of easy synthesis, strong designability, and abundant luminescence sites. By carefully designing the structure and fluorescence properties of this composite material, multi-channel and efficient H2S detection based on AuNCs is achieved. Among them, Pb-MOF can produce color changes visible to the naked eye due to the strong affinity between Pb clusters and H2S, and can be used as a colorimetric signal for H2S detection. This combination not only provides an ideal platform for efficient immobilization of AuNCs, but also gives the sensor dual-channel detection capabilities of fluorescence and colorimetry, and has excellent anti-interference ability, realizing rapid detection of hydrogen sulfide. Summary of the invention

[0005] The object of the present invention is to provide a fluorescence / colorimetric dual-mode sensor for hydrogen sulfide and a preparation method thereof in view of the deficiencies of the prior art.

[0006] The technical solution adopted by the present invention is as follows:

[0007] A preparation method of a fluorescence / colorimetric dual-mode sensor for hydrogen sulfide detection comprises: in-situ compounding of gold nanoclusters with lead-based metal-organic framework materials to obtain a gold nanocluster / metal-organic framework composite material, then uniformly mixing the composite material with sodium alginate to obtain a casting liquid, then taking the casting liquid and applying it on a substrate for scraping, and then forming and cleaning to obtain the sensor.

[0008] In the above technical solution, further, the gold nanoclusters are prepared by mixing chloroauric acid tetrahydrate with water, then adding glutathione solution, heating and stirring, wherein the molar ratio of chloroauric acid tetrahydrate to glutathione is 1:1.5-2.

[0009] Furthermore, the in-situ composite specifically includes the following: first preparing a metal salt solution of a lead-based metal-organic framework and an organic ligand solution at a certain temperature, adding a gold nanocluster solution to the organic ligand solution, and then dropping the metal salt solution thereinto, stirring the reaction at the temperature, washing with deionized water after the reaction, filtering and drying to obtain a gold nanocluster / metal-organic framework composite material.

[0010] Furthermore, the metal salt is lead nitrate, lead acetate or lead chloride.

[0011] Furthermore, the molar ratio of the metal salt to the organic ligand is 1:1-2.

[0012] Furthermore, the mass ratio of the gold nanoclusters to the lead in the lead-based metal-organic framework material is 1:40-60.

[0013] Furthermore, the gold nanoclusters / metal-organic framework composite material and sodium alginate are added to water and mixed, and stirred to obtain a casting liquid. The casting liquid is applied on a substrate by scraping, and then immersed in a calcium nitrate solution of a certain concentration for cross-linking and molding. The film is then rinsed with water to obtain a thin film, namely a fluorescence / colorimetric dual-mode sensor for hydrogen sulfide detection.

[0014] Furthermore, the mass concentration of sodium alginate in the casting solution is 0.02-0.05 g / mL, and the concentration of calcium nitrate is 30-50 mM.

[0015] Furthermore, the film has a thickness of 150 to 400 μm.

[0016] A fluorescence / colorimetric dual-mode sensor for hydrogen sulfide detection prepared by any of the above methods is used for on-site detection of hydrogen sulfide.

[0017] The principle of the present invention is as follows: the present invention introduces gold nanoclusters into metal-organic framework materials through an in-situ composite method to construct a composite material with dual-mode response performance. Due to the spatial confinement effect of Pb-MOF, the intramolecular motion of the gold nanoclusters is restricted, thereby significantly improving the fluorescence intensity of the gold nanocluster / metal-organic framework composite material. In addition, the material cleverly combines the excellent fluorescence properties of the gold nanoclusters and the chemical reaction properties of the Pb clusters in the MOF, thereby achieving high sensitivity and high selectivity detection of hydrogen sulfide in the fluorescence and colorimetric channels.

[0018] Compared with the existing methods, the present invention has the following advantages and beneficial effects:

[0019] (1) Compared with pure gold nanoclusters, the fluorescence performance of the gold nanocluster / metal-organic framework composite material prepared by the present invention is significantly improved.

[0020] (2) Compared with gold nanoclusters, the sensor prepared by the present invention has the advantages of rapid response to hydrogen sulfide, high sensitivity and high selectivity.

[0021] (3) The colorimetric and response dual response characteristics of the sensor prepared by the present invention can provide two different signals for self-verification and self-correction, thereby improving the reliability of hydrogen sulfide detection.

[0022] (4) After the film of the present invention is immersed in an actual hydrogen sulfide solution for 3-5 minutes, portable real-time detection of hydrogen sulfide can be achieved.

[0023] (5) Compared with the metal-organic framework powder probe, the film of the present invention avoids the agglomeration of metal-organic framework material powders, exposes more reaction sites, and improves the sensitivity and accuracy of detection. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a schematic diagram of the preparation process of the gold nanocluster / metal-organic framework composite material of the present invention;

[0025] Figure 2 It is the fluorescence emission spectrum of the pure gold nanocluster, metal-organic framework material and gold nanocluster / metal-organic framework composite material under 395nm excitation.

[0026] Figure 3 It is the fluorescence response of (b) gold nanoclusters and (a) gold nanoclusters / metal-organic framework composite materials of the present invention to a certain concentration of H2S.

[0027] Figure 4 These are the fluorescence and colorimetric images of the gold nanocluster / metal-organic framework hydrogel film of the present invention exposed to different hydrogen sulfide concentrations. DETAILED DESCRIPTION

[0028] The technical solution of the present invention will be further explained below in conjunction with embodiments, but these examples do not limit the protection scope of the present invention. On the basis of the technical solution of the present invention, various modifications or variations that can be made by those skilled in the art without creative work are still within the protection scope of the present invention.

[0029] Embodiment 1:

[0030] (1) Preparation of gold nanoclusters: Mix chloroauric acid tetrahydrate (1%, 0.8 mL) with 8.7 mL ultrapure water, and then add 0.3 mL glutathione solution (100 mM). Gently stir at 70°C for 24 h to successfully obtain a gold nanocluster solution, which was stored at 4°C for subsequent experiments.

[0031] (2) Preparation of gold nanocluster / metal-organic framework materials: First, dissolve 0.36mmol of lead nitrate hexahydrate (120mg) in 4mL of deionized water to prepare a lead nitrate solution. Take a 100mL reaction container, dissolve 0.36mmol of 1,3,5-tricarboxylic acid (75.6mg) in 36mL of deionized water, and stir vigorously at 63°C for 1h. Add 2mL of the synthesized gold nanoclusters to the ligand solution, and then slowly add the lead nitrate solution to the reaction mixture, and continue stirring at 63°C for 1h. After the reaction is completed, wash with deionized water, filter, and dry at 60°C for 12h to obtain a gold nanocluster / metal-organic framework composite material ( Figure 1 ).

[0032] (3) Preparation of hydrogel film: Sodium alginate powder (100 mg) and gold nanocluster / metal-organic framework composite material (33 mg) were added to deionized water (5 mL), dissolved by mechanical stirring, and allowed to stand for 40 min to eliminate bubbles to obtain a casting solution. The above solution was taken with a pipette, a small drop was sucked on a glass slide, and a scraper was used to scrape it into a film, and then the glass slide was placed in a calcium nitrate aqueous solution (30 mM) for molding. The molding time was 3 min, and the film was taken out and washed with deionized water to obtain a gold nanocluster / metal-organic framework hydrogel film with a mass fraction of 25% and a film thickness of 250 μm.

[0033] The luminescence performance of the sensor was investigated. Compared with pure gold nanoclusters, the fluorescence intensity of the gold nanocluster / metal-organic framework composite material was enhanced by 5 times (e.g. Figure 2 ), which significantly improved the luminescence properties of gold nanoclusters.

[0034] The fluorescence response performance of the sensor to hydrogen sulfide was investigated. When a certain concentration of hydrogen sulfide was added, the fluorescence quenching rate of the sensor to hydrogen sulfide was as high as 73% ( Figure 3 ), significantly improving the sensitivity of detection. In addition, when the hydrogel film is exposed to different concentrations of hydrogen sulfide, the fluorescence intensity gradually decreases. Under ultraviolet light, the orange-red fluorescence of the film gradually weakens; under natural light, the color of the film can be observed to change from white to dark brown ( Figure 4 ), which indicates that the sensor has a good bimodal response to hydrogen sulfide analyte.

[0035] Example 2

[0036] (1) Preparation of gold nanoclusters: Mix chloroauric acid tetrahydrate (1%, 0.8 mL) with 8.7 mL ultrapure water, and then add 0.2 mL glutathione solution (200 mM). Gently stir at 70°C for 24 h to successfully obtain a gold nanocluster solution, which was stored at 4°C for subsequent experiments.

[0037] (2) Preparation of gold nanocluster / metal-organic framework composite material: First, 0.1mmol lead acetate trihydrate (37.93mg) was dissolved in 1mL deionized water to prepare lead acetate aqueous solution. Take a 20mL reaction container, dissolve 0.1mmol 1,3,5-benzenetricarboxylic acid (21mg) in 10mL deionized water, and stir vigorously at 63℃ for 1h. Add 0.5mL of synthesized gold nanoclusters to the ligand solution, and then slowly add the lead acetate solution to the reaction mixture, and continue stirring at 63℃ for 1h. After the reaction is completed, wash with deionized water, filter, and dry at 60℃ for 12h to obtain a gold nanocluster / metal-organic framework composite material.

[0038] (3) Preparation of hydrogel film: Sodium alginate powder (80 mg) and gold nanocluster / metal-organic framework composite material (20 mg) were added to deionized water (5 mL), dissolved by mechanical stirring, and allowed to stand for 40 min to eliminate bubbles to obtain a casting solution. The above solution was taken with a pipette, a small drop was sucked on a glass slide, and a film was scraped with a scraper. The glass slide was then placed in a Ca(NO3)2 aqueous solution (40 mM) for molding. The molding time was 3 min. The film was taken out and washed with deionized water to obtain a gold nanocluster / metal-organic framework hydrogel film with a mass fraction of 20% and a film thickness of 200 μm.

[0039] The luminescence performance of the sensor was investigated. Compared with pure gold nanoclusters, the fluorescence intensity of the gold nanoclusters / metal-organic framework composite material was enhanced by 2 times, which significantly improved the luminescence performance of gold nanoclusters.

[0040] The fluorescence response performance of the sensor to H2S was investigated. When a certain concentration of hydrogen sulfide was added, the fluorescence quenching rate of the sensor to hydrogen sulfide was as high as 65% compared with pure gold nanoclusters, which significantly improved the detection sensitivity. In addition, when the hydrogel film was exposed to different concentrations of hydrogen sulfide, the fluorescence intensity gradually decreased. Under the irradiation of ultraviolet light, the orange-red fluorescence of the film gradually weakened; under natural light, the color of the film can be observed to change from white to dark brown, indicating that the sensor has a good dual-mode response to the hydrogen sulfide analyte.

[0041] Example 3

[0042] (1) Preparation of gold nanoclusters: Mix chloroauric acid tetrahydrate (1%, 1 mL) with 8.7 mL of ultrapure water, and then add 0.2 mL of glutathione solution (150 mM). Gently stir at 70°C for 24 h to successfully obtain a gold nanocluster solution, which was stored at 4°C for subsequent experiments.

[0043] (2) Preparation of gold nanocluster / metal-organic framework composite material: First, 0.2mmol lead chloride (55.6mg) was dissolved in 2mL deionized water to prepare a lead chloride aqueous solution. Take a 50mL reaction container, dissolve 0.2mmol 1,3,5-benzenetricarboxylic acid (42mg) in 20mL deionized water, and stir vigorously at 63℃ for 1h. Add 1mL of the synthesized gold nanoclusters to the ligand solution, and then slowly add the lead chloride solution to the reaction mixture, and continue stirring at 63℃ for 1h. After the reaction is completed, wash with deionized water, filter, and dry at 60℃ for 12h to obtain a gold nanocluster / metal-organic framework composite material.

[0044] (3) Preparation of hydrogel film: Sodium alginate powder (120 mg) and gold nanocluster / metal-organic framework composite material (25 mg) were added to deionized water (5 mL), dissolved by mechanical stirring, and allowed to stand for 40 min to eliminate bubbles to obtain a casting solution. The above solution was taken with a pipette, a small drop was sucked on a glass slide, and a film was scraped with a scraper. The glass slide was then placed in a calcium nitrate aqueous solution (50 mM) for molding. The molding time was 3 min. The film was taken out and washed with deionized water to obtain a gold nanocluster / metal-organic framework hydrogel film with a mass fraction of 17% and a film thickness of 300 μm.

[0045] The luminescence performance of the sensor was investigated. Compared with pure gold nanoclusters, the fluorescence intensity of the gold nanoclusters / metal-organic framework composite material was enhanced by 3 times, which significantly improved the luminescence performance of gold nanoclusters.

[0046] The fluorescence response performance of the sensor to H2S was investigated. When a certain concentration of hydrogen sulfide was added, the fluorescence quenching rate of the sensor to hydrogen sulfide was as high as 73% compared with pure gold nanoclusters, which significantly improved the detection sensitivity. In addition, when the hydrogel film was exposed to different concentrations of hydrogen sulfide, the fluorescence intensity gradually decreased. Under the irradiation of ultraviolet light, the orange-red fluorescence of the film gradually weakened; under natural light, the color of the film can be observed to change from white to dark brown, indicating that the sensor has a good dual-mode response to the hydrogen sulfide analyte.

[0047] The above-described embodiments are only some of the preferred solutions of the present invention, but they are not intended to limit the present invention. A person skilled in the relevant technical field may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, any technical solution obtained by equivalent replacement or equivalent transformation falls within the protection scope of the present invention.

Claims

1. A method for preparing a fluorescence / colorimetric dual-mode sensor for hydrogen sulfide detection, characterized in that: include: The gold nanoclusters and the lead-based metal-organic framework material are in situ compounded to obtain the gold nanocluster / metal-organic framework composite material, and then the composite material is evenly mixed with sodium alginate to prepare a casting liquid, and then the casting liquid is scraped on the substrate, and then formed and cleaned to obtain the sensor.

2. The method for preparing the fluorescence / colorimetric dual-mode sensor for hydrogen sulfide detection according to claim 1, characterized in that: The gold nano clusters are prepared by mixing chloroauric acid tetrahydrate with water, then adding glutathione solution, heating and stirring, wherein the molar ratio of chloroauric acid tetrahydrate to glutathione is 1:1.5-2.

3. The method for preparing the fluorescence / colorimetric dual-mode sensor for hydrogen sulfide detection according to claim 1, characterized in that: The in-situ composite specifically includes the following steps: first preparing a metal salt solution of a lead-based metal-organic framework and an organic ligand solution at a certain temperature, adding a gold nanocluster solution to the organic ligand solution, then dropping the metal salt solution thereinto, stirring and reacting at the temperature, washing with deionized water after the reaction, filtering and drying to obtain a gold nanocluster / metal-organic framework composite material.

4. The method for preparing the fluorescence / colorimetric dual-mode sensor for hydrogen sulfide detection according to claim 3, characterized in that: The metal salt is lead nitrate, lead acetate or lead chloride.

5. The method for preparing the fluorescence / colorimetric dual-mode sensor for hydrogen sulfide detection according to claim 3, characterized in that: The molar ratio of the metal salt to the organic ligand is 1:1-2.

6. The method for preparing the fluorescence / colorimetric dual-mode sensor for hydrogen sulfide detection according to claim 1, characterized in that: The mass ratio of the gold nano clusters to the lead in the lead-based metal-organic framework material is 1:40-60.

7. The method for preparing the fluorescence / colorimetric dual-mode sensor for hydrogen sulfide detection according to claim 1, characterized in that: The gold nanoclusters / metal-organic framework composite material and sodium alginate are added to water and mixed, and stirred to obtain a casting liquid. The casting liquid is applied on a substrate by scraping, and then immersed in a certain concentration of calcium nitrate solution for cross-linking and molding. The film is then rinsed with water to obtain a thin film, which is a fluorescence / colorimetric dual-mode sensor for hydrogen sulfide detection.

8. The method for preparing the fluorescence / colorimetric dual-mode sensor for hydrogen sulfide detection according to claim 7, characterized in that: The mass concentration of sodium alginate in the casting solution is 0.02-0.05 g / mL, and the concentration of calcium nitrate is 30-50 mM.

9. The method for preparing the fluorescence / colorimetric dual-mode sensor for hydrogen sulfide detection according to claim 8, characterized in that: The film thickness is 150-400 μm.

10. A fluorescence / colorimetric dual-mode sensor for hydrogen sulfide detection, characterized in that: The sensor is prepared by the method according to any one of claims 1 to 9 and is applied to on-site detection of hydrogen sulfide.

Citation Information

Patent Citations

  • Metal organic frame fluorescent probe and application thereof in hydrogen sulfide detection

    CN105968145A

  • Method of coating MOF to improve photostability of gold nanocluster and application thereof

    CN108213414A

  • Carbon-gold nanocluster ratio fluorescent sensor microsphere as well as construction and application thereof

    CN108226484A

  • Hydrogen sulfide detection method based on metal nanocluster

    CN114047169A

  • Gold and silver double-metal nanocluster for sulfide visual detection and preparation method of gold and silver double-metal nanocluster

    CN116144352A

Cited By

  • Responsive aerogel and use thereof

    WO2026153144A1